(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This expanded and enhanced article provides a deep scientific analysis of the theoretical, methodological, and practical foundations of cash accounting in modern enterprises. The study clarifies the conceptual essence of cash flows, evaluates the role of cash management in ensuring financial stability, and examines the integration of national standards with IFRS requirements, especially IAS 7. The methodological basis is significantly broadened to include theoretical–conceptual analysis, comparative assessment, regulatory evaluation, and digital transformation research. Particular emphasis is placed on the impact of ERP systems, AI-driven accounting tools, and cloud technologies on the accuracy, speed, and transparency of cash accounting. The results demonstrate that strong documentation, internal control, and automation are key factors strengthening payment discipline and minimizing accounting risks. The article also provides strategic recommendations for modernizing cash accounting systems in Uzbekistan, enhancing compliance with international standards, and improving financial decision-making. The study contributes to the advancement of accounting methodology by proposing more integrated and technology-oriented approaches to cash flow management.